2022
DOI: 10.3390/metabo12111132
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic Acid Promotes Lung Metastasis of Melanomas via the TLR4/TRIF-Peli1-pNF-κB Pathway

Abstract: A high-fat diet plays an important role in aggravating cancers. Palmitic acid (PA) is one of the components of saturated fatty acids; it has been reported to promote tumor proliferation in melanomas, but the signal transduction pathway mediated by palmitic acid remains unclear. This study showed that palmitic acid can promote the lung metastasis of melanomas. Moreover, the interaction between palmitic acid and toll-like receptor 4 (TLR4) was predicted by molecular docking. The experimental results proved that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Our Previous studies have shown that PA can promote the occurrence and development of melanoma [16] ; however, the underlying mechanism has not been fully elaborated. In the present study, we found that in a high PA environment, IL-17A helps PA to promote the metastasis of melanoma by targeting CPT1A with ATF2 (Figure 8).…”
Section: Discussionmentioning
confidence: 92%
“…Our Previous studies have shown that PA can promote the occurrence and development of melanoma [16] ; however, the underlying mechanism has not been fully elaborated. In the present study, we found that in a high PA environment, IL-17A helps PA to promote the metastasis of melanoma by targeting CPT1A with ATF2 (Figure 8).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the reproductive performance of rabbits was improved due to the (PUFA)-enriched diet [ 99 ]. On the other hand, palmitic acid derived from palm lung metastasis of melanomas, indicating the increased proliferation rate of the cells [ 98 ]. Furthermore, carcinogenesis and the role of fatty acids was investigated in female rats after consumption of sunflower, rapeseed, olive, or coconut oil.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, oxidative phosphorylation in the mitochondria is upregulated, and the Krebs cycle remains intact, in order to support anti-inflammatory macrophage responses [19] . The plasticity of macrophage inflammatory polarization is governed by tightly regulated metabolic pathways that can be disrupted by excessive exposure to dietary SFAs, including PA [12,16,24] . PA is the most common SFA found in the human body (20%-30% total FAs) and is enriched in meat, dairy products (50%-60% of total fats), and is nearly 30% of total fats in breast milk [2,25] .…”
Section: Pa Mediates Macrophage Metabolism and Functionmentioning
confidence: 99%
“…In contrast, oxidative phosphorylation in the mitochondria is upregulated, and the Krebs cycle remains intact, in order to support anti-inflammatory macrophage responses [ 19 ] . The plasticity of macrophage inflammatory polarization is governed by tightly regulated metabolic pathways that can be disrupted by excessive exposure to dietary SFAs, including PA [ 12 , 16 , 24 ] .…”
Section: Pa Mediates Macrophage Metabolism and Functionmentioning
confidence: 99%
See 1 more Smart Citation